Review of Online Sales Management Using Ecommerce At CV Jims Honey Official Jakarta - Intan Kusuma Dewi; Indra Prana (Jurnal Scientia, 2023)
Handling online orders is a series of order management processes that arise from online customer purchases, from receiving orders, printing shipping labels or packing slips, fulfilling orders, and submitting them to courier expeditions to be sent to the recipient's address. This study aims to determine the procedure for handling online orders at CV Jims Honey Official. The method used is descriptive qualitative with interviews, observation, and documentation study. The results of this study indicate that CV Jims Honey Official has three types of procedures for handling online orders based on the payment method, namely orders with a balance or credit payment method, cash payments, and payments through the marketplace using receipts. The total online orders entered on the e-commerce website https://jimshoneyindonesia.com/ during the study period were 5671. In handling these orders, several divisions are involved, which are also not free from obstacles in the implementation. Still, these obstacles can be overcome to fulfill customer or reseller orders.